Education and empowerment: Voices from Ugandan youth - Simone Datzberger (Austrian Foundation for Development Research (ÖFSE), 2022)
Despite the fast-growing body of literature on education and empowerment, young people's perception of their own educational setting has not received adequate attention in advancing our understanding of the empowering but also di sempowering elements of education. This is especially the case for the sub-Saharan African context. Addressing this gap, this study lets 497 Ugandan youth speak for themselves in the scope of a questionnaire. The diversity of young people's responses shows that experiences of empowerment through formal education differ significantly among individuals. By drawing on the work of Stromquist, this paper broadly relates young people's responses to cognitive (e.g.: critical understanding of one's reality), psychological (e.g.: feeling of self-esteem), political (e.g.: awareness of power inequalities and the ability to organize and mobilize) and the economic (e.g.: capacity to generate independent income) dimensions of empowerment through education. While the majority of youth indicated that they feel psychologically empowered th rough formal education, perceptions differed significantly in regard to economic empowerment. Besides, political or cognitive aspects of empowerment appear to happen outside and not in schools. A notable majority (75 %) feels disempowered by the many political, economic andsocial barriers they are facing outside their education, suggesting that education alone is not the magic bullet for systemic change at large.
Keywords: 330; Education; Empowerment; Youth; Uganda